THE CHEMICAL AND SENSORYCHARACTERISTICS AND THE SMOKING YIELD OF SMOKED CATFISH (Hemibagrusnemurus) PROCESSED AT DIFFERENT SMOKING TIME - Nurma Yunita; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to evaluate the chemical, sensory and smoking yields of cultivated catfish (Hemibagrus nemurus). The samples were the catfish at the weight of 250 gs/eachobtained from thecultivation cagesin. Kampar River in the village of Sungai Paku in the Regency of Kampar the Province of Riau. The catfish were smoked in relatively low smoking temperature in between 50-70 C for different smoking time, namely: 4, 5, 6, and 7 hours. The smoked fish were observed for their smoking yield, chemical and sensory quality. The results indicated that the highest value of smoking yield was found in the catfish smoked for 4 hours (75%), followed by those smoked for 5 hours (65,33%), 6 hours (56,66%) and 7 hours (43,46%). The highest content of fat (11,72%) and water (50,61%) were found in 4-hour smoked catfish. The highest protein content (50,59%), as well as ash content (2,47%), were found in the catfish smoked for 7 hours. Overall, the highest score of sensory value of the smoked catfish was shown by the 7 hours smoking time, at average score of (8.10), and significantly different to catfish smoked for 4 (7,07), 5 (7,44), and 6 hours (7,91).Keywords: Chemical value, Hemibagrus nemurus, sensory value, smoked fish, smoking yield